THE RELATIONSHIP BETWEEN RESPONSE TIME AND OUTPATIENT SATISFACTION AT SAMBAU HEALTH CENTER - Sri Muharni; Utari Christya Wardhani; Ranita Elsa (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2026)
Patient satisfaction is an essential indicator for assessing healthcare service quality, particularly in primary healthcare facilities such as Community Health Centers (Puskesmas). Waiting time or service response time is considered a critical factor influencing patients’ perceptions of service quality. This study aimed to examine the relationship between response time and patient satisfaction. A quantitative correlational study with a cross-sectional design was conducted. A total of 216 respondents were selected using purposive sampling. Response time was measured using a stopwatch, and patient satisfaction was assessed using a SERVQUAL-based questionnaire. Data were analyzed using the Chi-square test. The results indicated a statistically significant relationship between response time and patient satisfaction (p < 0.001). More than half of the respondents experienced response times exceeding the service standard (>60 minutes) (53.7%), while 46.3% received services within the standard time. Regarding satisfaction levels, 53.2% of respondents reported dissatisfaction, whereas 46.8% were satisfied. The findings suggest that shorter response times are associated with higher patient satisfaction. Therefore, optimizing service workflows and improving waiting time efficiency are recommended to enhance service quality in primary healthcare settings. Future research should incorporate additional factors, including healthcare providers’ communication quality and patients’ expectations, to provide a more comprehensive analysis